Information content of dividend changes : cash flow signalling, dividend clientele and free cash flow hypotheses / Norhayati Mohamed ... [et al.] - Mohamed, Norhayati; Abdul Hamid, Mohamad Ali; Md Nassir, Annuar; Mohamed, Shamsher (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
The study aims to identify the type of information that firms are trying to convey when they change dividend. The first step is to test the relationship between unexpected dividend changes and stock prices by employing the event study methodology. The next step is to evaluate the information content of dividend changes in the context of three hypotheses: the cashflow signaling hypothesis, the dividend clientele hypothesis and the free cashflow hypothesis. Past explanation to the effect of dividend changes on stock prices is that firms are signalling their current and/or future cashflow of the firm, or known as the cashflow signalling hypothesis. Later studies have incorporated other explanations, which are the dividend clientele hypothesis and the free cash flow hypothesis. Regression analysis is applied to study the wealth effect of dividend changes on stock prices and to test for the three hypotheses. The effect of firm size on the relationship between dividend changes and stock prices are also analysed by using total assets per share as the proxy variable for firm size. The findings show a significant relationship between unexpected dividend changes and stock prices, which also constitute support for the cash flow signalling hypothesis. Mixed support is found for the dividend clientele hypothesis while strong support is found for the free cash flow hypothesis.